Prophylaxis and treatment of invasive aspergillosis with voriconazole, posaconazole and caspofungin - review of the literature - Karthaus M (European Journal of Medical Research, 2011)
Abstract Major progress for the management of invasive aspergillosis has come from the introduction of new antifungals since the late 1990s. Although mortality of invasive aspergillosis remains as high as 30-50%. Backbone of management are prophylaxis, early diagnosis and early initiation of antifungals for reduction of invasive aspergillosis related mortality. Randomized trials have been undertaken for the prophylaxis as well as treatment of invasive aspergillosis in the last two decades. Posaconazole is recommended for prophylaxis against aspergillosis in patients treated for acute myelogenous leukemia, myelodysplastic syndrome or patients with graft versus host disease after allogeneic transplantation. Efficacy has been shown for first-line therapy of invasive aspergillosis with voriconazole and liposomal amphotericin B. Gastrointestinal resorption for the azoles posaconazole, voriconazole and itraconazole differ considerably. While oral voriconazole resportion is reduced when taken with food, posaconazole has to be taken with fatty food for optimal intestinal resorption. Beside all advances in the management of invasive aspergillosis important questions remain unresolved. This article reviews the current state of prophylaxis and treatment of invasive aspergillosis and points out clinicians unmet needs.